APPLICATION OF OCCUPATIONAL HEALTH AND SAFETY (K3) CONSTRUCTION PROJECT IN WEST DISTRICT KUTAI - TON, HARIS (KURVA S JURNAL MAHASISWA, 2014)
Occupational Health and Safety (K3) is a very important issue and a seriousdiscussion in the construction industry today. The construction industry is listedas one of the dangerous industry, where the rate of accidents and occupationaldiseases are diseases caused by work that could potentially still quite high. In thiscase the performance of safety and health is as important as productivity, moraleand operational cost control at all. Accident happen anytime and anywhere and tosiaapun.Any company employing many 100 (one hundred) or more and / or containspotential dangers posed by The characteristics of the production process ormaterial dapatmengakibatkan workplace accidents such as explosions, fire,pollution and occupational diseases shall implement a system of occupationalsafety and health management (K3). K3 management system shall be implementedby administrators, employers and the entire workforce as a whole in accordancewith the regulations of the Minister of Manpower No. 05/Men/1996 onKeselamatanm Work Management System.Work Management problem became the first affair as aspects that must beconsidered in the implementation of projects, especially in the construction phase.This is due at this stage because they collected a large amount of labor in a verynarrow area. Plus the nature of the construction workers are prone to accidentssuch as high elevation, power, temperature, transporting or lifting heavy objectsand others.Elements of the safety program and the most important is the company'spolicy statement, organization and personnel, maintaining working conditions tomeet the requirements for safety, make a report and analysis of the causes ofaccidents and provide first aid facilities.